Immunogenicity and reactogenicity of inactivated SARS-CoV-2 vaccines in healthy adults - Wu, Yufei; Huang, Ping; Xu, Mingjie; Zhao, Qianqian; Xu, Yihui; Han, Shuyi; Li, Huanjie; Wang, Yunshan (Frontiers in Immunology, 2023)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) are is highly pathogenic to humans and hasve caused the ongoing coronavirus disease 2019 (COVID-19) pandemics for almost three years. Vaccines are one of the efficient ways for to preventing the viral infection rate of virus. After COVID-19 vaccination, the monitoring of the dynamic change monitoring ofin neutralizing antibodies is necessary to deternine, which will be valuable to the way of booster shotsrequirements. We estimated the effectiveness of the inactivated vaccines by monitoring dynamic SARS-CoV-2 neutralizing antibodies in two for over 2 years. Additionally, Wewe also investigated the immune featuresactivation of T lymphocytes (CD3+ T cells) with respect to activation after three doses of the inactivated vaccine. The Rresults showed that the rate of reduction of SARS-CoV-2 neutralizing antibody levels gradually showed gradually after each booster dose. The IgG/ + IgM level of at 9 months after the third vaccination was were significantly higher than those at 6 months after the second vaccination dose (p＜0.0001). The expression of CD25+T cell in 18--35 age group was significantly higher than that in the other groups. The expression of CD25+CD8+ in 55-70 age group was significantly lower than 35-55 (P<0.01) and 18-25 (P<0.001). The expression of CD25+CD19+ in 55-70 age group was significantly lower than 35-55 (p＜0.001) and 18-35 (p＜0.0001). At the 9Nine months after the third vaccination dose (the time of last blood sample collection), the expression of CD25+T cell in the 18--35 years oldage group was significantly higher than that at 6 months after the second vaccinationdose. CD25+T cell in the 18-35 years old group was significantly higher than 6 months after the second vaccination. CD25, a late activation marker of lymphocytes and high-activity memory T cell subgroup, shown exhibited the higher levels in at the later stages of theafter vaccination. The COVID-19 booster vaccination in the elderlyolder adults and regular testing of SARS-CoV-2 neutralizing antibodies are recommended. The bBooster doses should be given administered if the antibody level falls below the 30% inhibition rate.